Effects of Reactive Oxygen Species on Mitochondrial Content and Integrity of Human Anastomotic Colorectal Dehiscence: A Preliminary DNA Study. (2011) - Potenza, Lucia; Calcabrini, Cinzia; De Bellis, Roberta; Guescini, Michele; Mancini, Umberto; Cucchiarini, Luigi; Nappo, Gennaro; Alloni, Rossana; Coppola, Roberto; Dugo, Laura; Dachà, Marina
Abstract : BACKGROUND: Anastomotic dehiscence is one of the most severe complications of colorectal surgery. Gaining insight into the molecular mechanisms responsible for the development of anastomotic dehiscence following colorectal surgery is important for the reduction of postoperative complications. OBJECTIVE: Based on the close relationship between surgical stress and oxidative stress, the present study aimed to determine whether a correlation exists between increased levels of reactive oxygen species and colorectal anastomotic dehiscence. METHODS: Patients who underwent surgical resection for colorectal cancer were divided into three groups: patients with anastomotic dehiscence (group 1); patients without dehiscence who underwent neoadjuvant radiochemotherapy (group 2); and patients without anastomotic dehiscence who did not undergo neoadjuvant radiochemotherapy (group 3). Quantitative polymerase chain reaction and real-time polymerase chain reaction assays were performed to measure nuclear DNA and mitochondrial DNA (mtDNA) content, and possible oxidative damage to nonmalignant colon and rectal tissues adjacent to the anastomoses. RESULTS: mtDNA content was reduced in the colon tissue of patients in groups 1 and 2. Rectal mtDNA was found to be more damaged than colonic mtDNAs in all groups. The 4977 bp common deletion was observed in the mtDNA of tissues from both the colon and rectum of all patients. DISCUSSION: Patients in groups 1 and 2 were more similar to one another than to group 3, probably due to higher levels of reactive oxygen species in the mitochondria; the greater damage found in the rectum suggests that dehiscence originates primarily from the rectal area. CONCLUSIONS: The present study of mtDNA analyses of normal human colon and rectal tissues from patients with colorectal cancer is among the first of its kind.